Proximities and the emergence of regional industry: evidence of the liability of smallness in Malta. Issue 2 (1st February 2020) - Yamamura, Sakura; Lassalle, Paul
ABSTRACT: The interplays of different types of proximities are crucial to the emergence of new industries, including entrepreneurial ecosystems as pillar of the competitive advantage in regions. Though proximities can be advantageous, negative aspects on the economic development have also been discussed, leading to the discussion of the so-called proximity paradox. To better understand the effective functioning of these proximities, it must be concretized which institutional actors play a role, and how their collaboration and thus their proximity constellations contribute to the regional development. Based on empirical evidence of Malta, this paper operationalizes the different proximities types and conceptually investigates the different proximities between institutional actors in building a new regional industry, i.e. the gaming industry. The case of the Maltese gaming industry illustrates how regions with limited size and resource-scarcity, thus high proximities between actors (also prevalent in city-states and peripheral regions), can still defy the odds of the liability of smallness and, thus the proximity paradox. Results of this in-depth study shows how collaborative endeavour of proximate institutional actors can contribute to developing an effective entrepreneurial environment and the emergence of a new regional industry.